Further Geometric Properties of a Subclass of Univalent Functions - A. Oyekan, Ezekiel (International Journal of Advanced Mathematical Sciences, 2020)
This present paper aims to investigate further, certain characterization properties for a subclass of univalent function defined by a generalized differential operator. In particular, necessary and sufficient conditions for the function Â to belong to the subclass Â is established. Additionally, we provide the ð›…-neighborhood properties for the function Â by making use of the necessary and sufficient conditions. The results obtained are new geometric properties for the subclassÂ Â